PENGARUH KOMPENSASI, LINGKUNGAN KERJA KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. SINAR BINTANG MANDIRI MEDAN (STUDI KASUS) - Ritonga, Sinar; Pasaribu, Tiara Kristina; Simatupang, Eduard (UNIKA Santo Thomas, 2022)
This research aims to find out the extent of the effect of compensation, work environment, safety and health (K3) on employee performance of PT. starlight is self-contained terrain. Data collection is done through questionnaires, interviews and documentation techniques. The research method used was quantative, with 74 respondents taken using saturated sampling and census. The results of this study showed that the variables of compensation, work environment, occupational safety and health (K3) together (simultaneously) had a positive and significant effect on the performance of PT employees. Self-Contained StarLight. While partially showing that compensation has a positive and significant effect on the performance of employees of PT. Medan independent starlight with a regression coefficient value of 0.349 and a significance value of 0.000 < 0.05 (less than the error tolerance value). The work environment has a positive and significant effect on the performance of PT employees, sinar Bintang Mandiri Medan with a regression coefficient value of 0.371 and a significance value of 0.000 < 0.05 (less than the error tolerance value). Occupational safety and health (K3) has a positive and significant effect on the performance of employees of PT. Mandiri Medan star beam with regression coefficient value 0.319 and significance value of 0.016 < 0.05 (greater than the error tolerance value).